The Outreach on Basic Financial Management and Entrepreneurial Self-Reliance for Micro-Entrepreneurs, Members of Aspikmas Banyumas - Hengky Widhiandono; Selamet Eko Budi Santoso; Purnadi (Journal of Society, Community and Business Development, 2025)
A Good financial management and a self-reliance are crucial for the sustainability of micro-enterprises. In Banyumas Regency, members of the Banyumas Association of Micro, Small, and Medium Enterprises (ASPIKMAS) often face challenges in basic financial management and entrepreneurial Self-Reliance. This outreach program aims to improve basic financial literacy and self-reliance among ASPIKMAS members through the use of the Lamikro application and sessions on techniques for enhancing entrepreneurial self-reliance. The program results are an increase in participants’ understanding of basic financial reports and effectively managing their entrepreneurial self-reliance. Participants reported feeling more confident and independent in making business decisions. This initiative is expected to have a lasting positive impact on micro-entrepreneurs in Banyumas.